Pengaruh Intellectual Capital terhadap Kinerja Keuangan dengan Good Corpoprate Governance sebagai Variabel Mediasi - Set Asmapane; Annisa Abubakar Lahjie; Muhammad Ikbal; Zulfie Nur Risqi; Hartojo Fellisia Ersa (RELASI : JURNAL EKONOMI, 2021)
The emergence of a "new economy", which is principally driven by developments in information technology and science, has also sparked a growing interest in intellectual capital. One area that has attracted the attention of both academics and practitioners is the use of IC as an instrument to determine company value. management and reporting systems that have been established so far have continually lost their relevance because they are unable to provide essential information for executives to manage knowledge-based processes. Reporting on intellectual capital owned will be an added value for a company. So that reporting on intellectual capital will have an impact on improving financial performance. The implementation of Good Corporate Governance (GCG) is one of the governance systems considered to be able to provide changes for the company, so that the implementation of GCG is expected to have an impact on the wider disclosure of intellectual capital owned by a company and will have an impact on the better company performance. This research was conducted using a sample of manufacturing companies listed on the Jakarta Stock Exchange with a three-year research period, 2017 to 2019, with a sample size of 65 manufacturing companies and in analyzing the existing data, the SmartPLS tool was used. The results showed that the Intellectual Capital variable had a positive and significant influence on the company's financial performance variable, and the Good Corporate Governance variable did not have the effect to mediate the relationship between the Intellectual Capital variable and the Financial Performance variable. Keywords: Financial Performance, Intellectual Capital, Gcg